Photoredox-catalyzed intramolecular nucleophilic amidation of alkenes with β-lactams - Giraldi, Valentina; Magagnano, Giandomenico; Giacomini, Daria; Cozzi, Pier Giorgio; Gualandi, Andrea (Beilstein Journal of Organic Chemistry, 2024)
The direct nucleophilic addition of amides to unfunctionalized alkenes via photoredox catalysis represents a facile approach towards functionalized alkylamides. Unfortunately, the scarce nucleophilicity of amides and competitive side reactions limit the utility of this approach. Herein, we report an intramolecular photoredox cyclization of alkenes with β-lactams in the presence of an acridinium photocatalyst. The approach uses an intramolecular nucleophilic addition of the β-lactam nitrogen atom to the radical cation photogenerated in the linked alkene moiety, followed by hydrogen transfer from the hydrogen atom transfer (HAT) catalyst. This process was used to successfully prepare 2-alkylated clavam derivatives.
Keywords: β-lactam; acridinium photocatalyst; alkenes; amides; intramolecular radical reaction; photoredox catalysis